2017
DOI: 10.1016/j.otsr.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacies of coracoclavicular ligament reconstruction using suture anchor versus hook plate in the treatment of distal clavicle fracture

Abstract: Level II, low-powered prospective randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Despite high rates of union, the use the HP is particularly contentious due to high rates of irritation requiring hardware removal reported in the literature (62.5%) [ 6 ]. This has led to some authors routinely removing HP metalwork at four-six months to reduce the risk of postoperative complications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite high rates of union, the use the HP is particularly contentious due to high rates of irritation requiring hardware removal reported in the literature (62.5%) [ 6 ]. This has led to some authors routinely removing HP metalwork at four-six months to reduce the risk of postoperative complications [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several comparative studies, CC flexible fixation has been reported as providing satisfactory results. Yan et al 52) compared the clinical results of CC ligament reconstruction using suture anchors with those using an autologous gracilis tendon (21 patients) and a hook plate (21 patients) in a total of 42 patients. All patients in both groups achieved bony union without major complications and satisfactory clinical outcome at the last follow-up.…”
Section: Hook Platementioning
confidence: 99%
“…Asadollahi and Bucknill 2 reported no significant difference in functional outcome and union rate among hook plate, CC stabilization, and locking plate in a systematic review comprising 634 patients. However, their most important limitation was the inclusion of the study of Yan et al, 70 which is biased because it primarily excluded patients with nonunions. Boonard et al 4 compared the functional outcome of 5 operative methods (CC fixation, hook plate, locking plate, TBW, and transacromial KW fixation) in 547 patients and showed that CC fixation and locking plates resulted in higher CMS and UCLA scores when compared with the other surgical methods.…”
Section: Discussionmentioning
confidence: 99%